FEATURES TOOTH DEPOSITS REMOVAL DURING ORAL HEALTH PROFESSIONAL - Pavlenko, S.A. (World of Medicine and Biology, 2012)
Are some reasons for changing the color of the teeth and plaque formation. The characteristics of a tool for removing dental plaque during professional oral hygiene.
Keywords: dental plaque; instruments to remove dental plaque